PERTIMBANGAN HAKIM TENTANG TUJUAN PELAKU TINDAK PIDANA DALAM PENJATUHAN PUTUSAN PENGADILAN - Rambu Susanti Mila Maramba (Yayasan Akrab Pekanbaru, 2019)
The judge has independent authority in giving decisions on court cases and rights granted by law. In the case of a criminal act, the legal process cannot be separated from the matter to be taken into consideration, namely the purpose or reason for spending in a criminal case. The reason for crime is always questioned by law enforcers (judges) in the process of proof, consideration and imposition of decisions.